RELEVANSI ANTARA KEPROFESIONALAN GURU DENGAN TUGAS MENGAJAR PADA MATA PELAJARAN SEJARAH (Studi Kasus di SMA Negeri Gorontalo) - Yusni Pakaya (Jurnal Inovasi, 2011)
This research aims to find out; history teacher's professionalism in SMA Negeri of Gorontalo City, and the performance of history teachinglearning and the relevancy of teacher professionalism to teaching task, history subject. This research is conducted at SMA Negeri, Gorontalo City. It is a descriptive qualitative research, technique of collecting the data using interview technique, observation and data. Quotation technique in this research is completely purposive sampling. This research results: (1) The professionalism of history teacher at SMA Negeri at Gorontalo City, commonly, does not fulfill the expected standard, because there are still many teachers, who are irrelevant to fields of study in teaching task. (2) The performance of history teaching-learning is not performed optimum yet. Some of teachers, they can be seen, less mastery teaching-learning material and method.